PENERAPAN COMMUNITY BASED CORRECTION DALAM SISTEM PEMASYARAKATAN DI INDONESIA - Deny Sifa; Mitro Subroto (Universitas Halu Oleo, 2022)
The purpose of this research is to know and understand the application of Community Based Correction in the Correctional System in Indonesia according to the concept of Communty Based Correctional which is a concept that is in line with the goal of correctional, namely social reintegration. This research method is descriptive using qualitative methods and a sociological approach. This research is an attempt to describe social phenomena that become a problem in community-based WBP development without performing a hypothesis and descriptive statistical calculations, not in a narrow sense. The results of the research after being identified, constructed, compiled and analyzed using qualitative methods based on theories, principles and legal norms related to the subject matter. The results show that alternative philosophies have developed, namely community-based corrections and restorative justice. These two philosophies are closely related to the goals expected in correctional facilities, namely to seek the reintegration of the WBP with the community. Community-based corrections are a type of coaching program for WBP at the end of their criminal period where they are given the opportunity to return to the midst of society with certain supervision or supervision.